MENDUDUKKAN PERAN HUKUM ISLAM DALAM PEMBANGUNAN HUKUM NASIONAL DI INDONESIA (Suatu Tinjauan Ketatanegaraan) - A.Kumedi Ja'far (Faculty of Law, Universitas Diponegoro, 2011)
The Indonesia law is the national laws which be based on the philosophy of Pancasi/a. The national laws which serve national interests filled with the values of unity in diversity, especially the value in religion. Therefore, it is clear that Islamic law have an important role in developing of the national legislation in Indonesia. It can be seen from some regulations such as the laws of marriage, heritage, waqaf and Agrarian. By the legalization of that laws as part of national laws, it can be said that Islamic laws have given the contribution in developing the national laws.